Lexical-semantic development of turkisms in russian language (Eurasian Journal of Philology Science and Education, 2015)
This article begins by explaining what Turkisms mean and how Turkic words are investigated nowadays. Currently, the Turkic languages are highly developed national languages with very broad social functions. This fact deserves special attention and is particularly relevant in our time – the time of real bilingualism. While considering the history of Russian-Turkic languages relations it was revealed that Turkic words began to be viewed in the Russian language in the second half of the XVIII century. Turkisms, in the process of their assimilation were subjected to all sorts of changes to obey the laws of the development of the Russian language, its functional and stylistic norms. Semantic changes of borrowings were brought about in three ways. The examples of such words are given in speech, in dialects and proverbs.
Keywords: Turkism; Russian language; lexical-semantic group; phonetics; grammar